2014
DOI: 10.1155/2014/793247
|View full text |Cite
|
Sign up to set email alerts
|

Linearization from Complex Lie Point Transformations

Abstract: Complex Lie point transformations are used to linearize a class of systems of second order ordinary differential equations (ODEs) which have Lie algebras of maximum dimension d, with d ≤ 4. We identify such a class by employing complex structure on the manifold that defines the geometry of differential equations. Furthermore we provide a geometrical construction of the procedure adopted that provides an analogue in IR 3 of the linearizability criteria in IR 2 .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Linearizability of such systems implies linearizability of the complex scalar equation constructed from it; the converse is not true; linearizability of the complex scalar equation does not imply linearizability of the system [3]. If the scalar ODE is linearizable and the resulting system is also linearizable, this procedure is called complex linearization.…”
Section: Preliminariesmentioning
confidence: 99%
“…Linearizability of such systems implies linearizability of the complex scalar equation constructed from it; the converse is not true; linearizability of the complex scalar equation does not imply linearizability of the system [3]. If the scalar ODE is linearizable and the resulting system is also linearizable, this procedure is called complex linearization.…”
Section: Preliminariesmentioning
confidence: 99%
“…arbitrary and non-linear, as given in Case 1. Equations (7) and (12), after some straightforward calculations, show that ς 1 = 1, ς 2 = 0, χ 1 = χ 2 = 0, and A 1 , A 2 are constants. Therefore, we have a single Noether-like operator X = ∂ ∂x .…”
Section: Noether-like Operators and First Integrals For Different Formentioning
confidence: 99%
“…For instance, the use of the complex variable technique to discuss linearization of systems of two second-order ODEs and PDEs has been presented in [6]. The procedure of converting a system of two second-order ODEs admitting Lie algebra of dimension d (d ≤ 4) into linearizable form with the help of complex Lie point symmetries of the base equation was given in [7]. Using semi-invariants, Mahomed et al [8] studied systems of two linear hyperbolic PDEs when they arise from a complex scalar ODE.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we reconsider a class of two-dimensional, systems of second order ODEs that is solved using complex methods [13]. There it was shown that, for this class of systems, dimensions of the Lie point symmetry algebra remain less than 5, while the base complex equations in most of the cases possess an eight-dimensional Lie and a five-dimensional Noether algebra.…”
Section: Noether Symmetries and Corresponding First Integralsmentioning
confidence: 99%
“…The explicit use of complex functions of complex or real variables is demonstrated in [7][8][9][10] where solvability of systems of DEs is achieved through Noether symmetries and corresponding first integrals. Furthermore, by employing complex symmetry procedures: the energy stored in the field of a coupled harmonic oscillator was studied in [11] and linearizability of systems of two second order ODEs was addressed in [12,13]. The complex procedure, indeed, has been extended to higher dimensional systems of second order ODEs [14] and two-dimensional, systems of third order ODEs [15].…”
Section: Introductionmentioning
confidence: 99%